2006
DOI: 10.1021/ja054872i
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cationic [2 + 2] Cycloaddition in a Divergent Total Synthesis of Hongoquercin A and Rhododaurichromanic Acid A

Abstract: An unusual polyene cyclization pathway that led to a divergent total synthesis of hongoquercin A and rhododaurichromanic acid A is described here. This work uncovered a unique cationic cyclobutane formation that could be relevant to the biosynthetic pathway for the formation of cyclobutane containing terpenoids in addition to rhododaurichromanic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 26 publications
4
30
0
1
Order By: Relevance
“…Our study has verified the reported absolute configuration of (+)‐ 1 as S through the assignment of the absolute configuration of (–)‐ 2 as 5 R ,8 S ,10 R with minimized computational cost and high reliability . In the only reference on 2 , Kurdyumov and Hsung synthesized the 9,15‐saturated derivative of 3 , hongoquercin A, as an enantiopure form.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Our study has verified the reported absolute configuration of (+)‐ 1 as S through the assignment of the absolute configuration of (–)‐ 2 as 5 R ,8 S ,10 R with minimized computational cost and high reliability . In the only reference on 2 , Kurdyumov and Hsung synthesized the 9,15‐saturated derivative of 3 , hongoquercin A, as an enantiopure form.…”
Section: Resultssupporting
confidence: 74%
“…The obtained compound (–)‐ 2 was then hydrolyzed to (–)‐ 3 (Scheme ). The determination of the absolute configurations of 1 and 2 was reported based on X‐ray crystallography and total synthesis …”
Section: Resultsmentioning
confidence: 99%
“…16 Direct excitation of stilbenes and the selective excitation of the charge-transfer (CT) complex at various temperatures succeeded in diastereodifferentiating the 2 + 2-photocycloadditions of (E)-and (Z)-stilbenes to bis[(R)-1methylpropyl]fumarate to produce p-truxinates. 17 The diastereoselective transannular de 2 + 2-photocycloaddition of ascorbic acid derivatives (19) produced polyoxacyclic structures (20,21) in high yields with high diastereocontrol. The adducts will be tested as chiral ligands for enantioselective reactions (Scheme 6).…”
Section: + 2-cycloadditionmentioning
confidence: 99%
“…Further manipulation of adduct (23) yielded rhododaurichromanic acid A (24) (Scheme 7). 19 Ruthenium-catalysed 2 + 2-cycloadditions of norbornenes with alkynes produced the corresponding exo-cyclobutenes in good yields. Regioselectivity was observed with various substituents on the C(2) position of the norbornenes.…”
Section: + 2-cycloadditionmentioning
confidence: 99%
“…We have also described the remote hydroxylation of the Me (23) and Me (24) groups of these natural triterpene compounds by a regioselective cyclopalladation process yielding other natural compounds with potentially interesting biological activities [16]. In addition, we have reported an initial study of the formation of several derivatives from oleanolic acid and maslinic acid with a cleaved C-ring [17 -19].…”
mentioning
confidence: 99%